2011
DOI: 10.4489/myco.2011.39.2.096
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Effect of DietaryLentinus edodeson Plasma, Feces and Hepatic Tissues in Hypercholesterolemic Rats

Abstract: We investigated diet supplementation with shiitake mushroom fruiting bodies on biochemical and histological changes in hypercholesterolemic rats. Six-wk old female Sprague-Dawley albino rats were divided into three groups of 10 rats each. A diet containing 5% Lentinus edodes fruiting bodies given to hypercholesterolemic rats reduced plasma total cholesterol, triglyceride, low-density lipoprotein (LDL), total lipid, phospholipids, and the LDL/high-density lipoprotein ratio by 34.33, 53.21, 75.00, 34.66, 25.73, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
(29 reference statements)
2
8
0
1
Order By: Relevance
“…The use of edible mushrooms has been prescribed in oriental medicine due to their hypocholesterolemic effects (Sun et al, 2007). Similar with our result, various studies (Kim et al, 2001;Yang et al 2002;Yoon et al, 2011) have confirmed that shiitake mushrooms lower blood serum cholesterol levels in rats and support the use of the mushrooms as a natural cholesterol lowering substances in the diet. In contrast, Mužić et al (2005) found no effect of L. edodes on the cholesterol content of egg yolk.…”
Section: Fatty Acid Composition and Cholesterol Concentration Of Egg supporting
confidence: 89%
See 1 more Smart Citation
“…The use of edible mushrooms has been prescribed in oriental medicine due to their hypocholesterolemic effects (Sun et al, 2007). Similar with our result, various studies (Kim et al, 2001;Yang et al 2002;Yoon et al, 2011) have confirmed that shiitake mushrooms lower blood serum cholesterol levels in rats and support the use of the mushrooms as a natural cholesterol lowering substances in the diet. In contrast, Mužić et al (2005) found no effect of L. edodes on the cholesterol content of egg yolk.…”
Section: Fatty Acid Composition and Cholesterol Concentration Of Egg supporting
confidence: 89%
“…Of particular interest are extracts derived from various mushrooms, as they are known to modulate immune response and stress reduction on poultry (Dalloul et al, 2006;Lee et al, 2010). Various studies have confirmed that the mushrooms can lower blood pressure and free cholesterol in plasma (Hobbs, 2000;Yoon et al, 2011), as well as accelerate the accumulation of lipids in the liver by removing them from circulation, and can prevent cardiovascular disease (Guillamón et al, 2010). Xu et al (2008) reported that the administration of polysaccharides from L. edodes significantly reduced serum total cholesterol, triglyceride, low-density lipoprotein cholesterol, and enhanced serum antioxidant enzyme activity and thymus and liver index in high-fat rats.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of TC and HDL-C in turmeric co-administered rats revealed that turmeric extract had significant capability to restore their levels when compared to the controls. This changes may be attributed to the inhibition of cholesterol absorption and biosynthesis, inhibition of biosynthesis of very-low-density lipoproteins, the precursor of LDL-C and acceleration of fractional turnover of LDL-C (Yoon et al 2011) as well as the increased in excretion of bile acids through the active compounds in this turmeric (Vahouny et al 1987). LPO is a well-established mechanism for oxidative stress, leading to cell injury (Sankar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We can mention β-glucans (lentinan) [29] , high proteins and essential amino acid levels [4] , [14] , vitamins (C, D, B 1 , B 2 , B 12 , niacin) [4] , [16] among others [4] . These compounds provide for L. edodes several therapeutic applications as antitumor activity [9] , [29] , antihyperlipidemic effect [28] , antioxidant [9] , and antiviral activity [26] .…”
Section: Introductionmentioning
confidence: 99%